Weed Management in Pastures and Rangeland—2017 - Brent A. Sellers; Jason A. Ferrell (EDIS, 2017)
Weeds in pastures and rangeland cost ranchers in excess of $180 million annually in Florida by reducing forage yield, lowering forage quality, and causing animal injury through toxicity or specialized plant organs (thorns and spines). Effective weed management begins with a healthy pasture. Weeds are seldom a serious problem in a well-managed, vigorously growing pasture. Good pasture management involves the proper choice of the forage species and variety, an adequate fertility program, controlled grazing management, and pest management (weeds, insects, and diseases). This 16-page fact sheet is a minor revision written by Brent Sellers and Jason Ferrell, and published by the Agronomy Department, December 2016.